Recent advances in the conversion of methane to synthesis gas - Tsang, S; Claridge, J; Green, M (1995)
A brief review on the recent developments of alternative routes for synthesis gas production, namely catalytic methane partial oxidation and methane reforming with carbon dioxide, is presented. Particular attention is given to reaction thermodynamics, catalyst formulation, reaction mechanism and problems of carbon deposition. © 1995.